New Image of Nature in Colors Of The Wind and Lihatlah Lebih Dekat Lyrics - Syabrina Sri Sulistyani; Yoga Sudarisman; Agry Pramita (Edukasi Lingua Sastra, 2026)
This study discusses how the relationship between humans and nature is represented in popular song lyrics through the perspective of Emerson's Transcendentalism. This study examines how song lyrics can represent alternative views of nature as personal and moral consciousness. This study is a literary critique that takes a mimetic and expressive approach, using comparative literature as an umbrella to compare the two objects of study. The objects of this study are the lyrics of the songs Colors of the Wind and Lihatlah Lebih Dekat, which are analyzed using Emerson's four functions of nature: Commodity, Beauty, Language, and Discipline. The results show that Colors of the Wind represents all four functions of nature, with an emphasis on criticism of the commodification of nature, colonialism, and moral learning through human-nature relations. Meanwhile, Lihatlah Lebih Dekat highlights the function of Language by describing nature as a symbolic medium that encourages reflection on nature. This difference shows that Transcendentalism is adaptable and remains relevant across language contexts, and can be used to read popular song lyrics as literary texts that represent individual awareness of nature.